Peran Guru dan Ibu sebagai Agen Pencegahan Tuberkulosis Anak di Lingkungan Sekolah dan Keluarga - Irma Hamisah; Farrah Fahdhienie; Fahrisal Akbar; Muhammad Iqhrammullah (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2026)
Childhood tuberculosis (TB) remains a public health problem in Indonesia, including in Aceh Besar Regency. Efforts to prevent childhood TB require the active involvement of teachers and mothers as key actors in school and family environments. This community service aims to describe the attitudes, roles, readiness, practices, and acceptance of childhood TB educational media among teachers and mothers as agents of childhood TB prevention. The service employed a descriptive quantitative design with a total of 20 respondents, consisting of teachers and mothers. Data were collected using a four-point Likert scale questionnaire. Data analysis was conducted descriptively by presenting frequency distributions, percentages, and mean scores. The results indicate that most respondents have a positive attitude toward childhood TB prevention (mean score 3.55), a good role as prevention agents (3.48), good readiness (3.50), good preventive practices (3.42), and very good acceptance of educational media (3.65). These findings suggest that teachers and mothers have significant potential as agents of childhood TB prevention in school and family settings. Strengthening their roles through guidance and integration of programs with health facilities is necessary to ensure the sustainability of childhood TB prevention efforts.